2019
DOI: 10.1248/bpb.b18-00638
|View full text |Cite
|
Sign up to set email alerts
|

BubR1 Is Essential for Thio-Dimethylarsinic Acid-Induced Spindle Assembly Checkpoint and Mitotic Cell Death for Preventing the Accumulation of Abnormal Cells

Abstract: Thio-dimethylarsinic acid (thio-DMA) was detected in human urine after exposure to inorganic arsenic and arsenosugars consumed by marine algae. Our previous studies have shown that thio-DMA disturbed the cell cycle progression and arrested cells in mitosis, though the biological significance or the mechanism by which thio-DMA-induced mitotic phase accumulation occurs is yet to be understood. In this study, we showed that thio-DMA promotes the phosphorylation of BubR1 protein, which is one of the constituents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Kita et al reported that BubR1 knockdown in Hela cells showed reduced formation of mitotic checkpoint complex and mitotic arrest induced by thio-dimethylarsinic acid. The mitotic index was significantly decreased associated with almost completely abolished cyclin B1 protein expression in the BubR1 knockdown cells, leading to an increased cell survival when exposed to thio-dimethylarsinic acid ( 39 ). Our data were consistent with this notion showing that sildenafil significantly amplified vincristine-mediated BubR1 phosphorylation and mitotic index, increasing cyclin B1 protein levels and ultimately sensitizing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kita et al reported that BubR1 knockdown in Hela cells showed reduced formation of mitotic checkpoint complex and mitotic arrest induced by thio-dimethylarsinic acid. The mitotic index was significantly decreased associated with almost completely abolished cyclin B1 protein expression in the BubR1 knockdown cells, leading to an increased cell survival when exposed to thio-dimethylarsinic acid ( 39 ). Our data were consistent with this notion showing that sildenafil significantly amplified vincristine-mediated BubR1 phosphorylation and mitotic index, increasing cyclin B1 protein levels and ultimately sensitizing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%